Almost \((\alpha/\eta)\)-\(\psi_\Gamma\)-Contraction in Induced Fuzzy Metric Space and Application to Fredholm Integral Equations - Saini, Rajesh Kumar; Kushwaha, Mukesh Kumar (Communications in Mathematics and Applications, 2022)
In this paper, we established a new class of almost \((\alpha/\eta)\)-\(\psi_\Gamma\)-contraction mapping in induced fuzzy metric space (FMS) and then proved the results for existence of fixed point theorem (FPT) for multi-valued mappings (MVMs) on the collection of non-empty closed subsets. In application, we prove the existence theorem for Fredholm integral inclusion (FII). An illustrative example also introduced in support of our main result.
Keywords: Almost \((\alpha/\eta)\)-\(\psi_\Gamma\)-contraction; Induced fuzzy metric space; Fredholm integral equation.